Experiences of discharge planning practices among Indonesian nurses: A qualitative study - Titis Kurniawan; Kittikorn Nilmanat; Umaporn Boonyasopun; Amelia Ganefianty (Belitung Raya Foundation, Indonesia, 2023)
Background: Discharge planning is vital to preventing hospital readmission, and nurses play a key role. The COVID-19 pandemic has posed challenges to hospital services that may persist or recur. Therefore, exploring nurses’ experiences with discharge planning practices before and during this pandemic is crucial. Objective: This study aimed to describe the experiences of discharge planning practices among nurses at an Indonesian tertiary hospital before and during the COVID-19 pandemic. Methods: A qualitative descriptive study design was used. Telephone interviews were conducted to collect data among ten nurses from March 2019 and continued between December 2020 and August 2021. Content analysis was done for data analysis. Results: Two main themes emerged: 1) Challenges in discharge planning practices and 2) Perceived discharge planning as a professional responsibility. Implementing the inpatient ward fusion policy as part of the hospital’s pandemic response presented greater challenges to nurses in coordinating care and performing discharge planning. Fear of COVID-19 infection, social distancing measures, and using personal protective equipment also affected how nurses delivered discharge education during the pandemic. However, the nurses sensed a greater responsibility to ensure the maintenance of essential components of discharge planning procedures to guarantee the patient’s capability to perform self-care at home. Conclusion: Nurses viewed discharge planning practices as their responsibility and continued them during the pandemic despite facing various challenges. In addition to recognizing the significance of nurses’ roles in discharge planning practices and overall patient care, it is crucial to anticipate and address the diverse working patterns and styles among healthcare professionals in unified wards, ensuring effective coordination.